The impact of globalization on Workers: an Analysis of Nigerian Public Service - Mohammed Lawan, Aminu; Mohd Ramli, Razlini (International Journal of Engineering and Technology, 2018)
Globalization is the increasing interaction of peoples, states or countries through the growth of the global trade, international flow of capital, ideas and culture. The paper discusses how privatization of public corporations and invention of information and communication technology (ICT) lead to the retrenchment and casualization of public servant. The aim of this study is to examines the impact of globalization on the public servant in Nigeria. The methodology involves the use of secondary data, through a systematic literature review which entails the document analysis of related matters. The findings reveal that globalization infringes on the right of a public servant by making them vulnerable without job security. The paper concludes that government must stop unfair labor practice such as retrenchment and casualization of workers, and improve good working conditions to make public servant more productive.Â